Proliferative activity of normal and neoplastic urothelium and its relation to epidermal growth factor and transferrin receptors. Issue 9 (September 1993) - Limas, C; Bair, R; Bernhart, P; Reddy, P
Abstract : AIMS--To investigate the proliferative activity (given by the Ki67 index) of the normal, atypical, and neoplastic urothelium and its relation to the cellular reactivity for the epidermal growth factor (EGFr) and transferrin (Tfr) receptors. METHODS--The Ki67 index and the level of EGFr and Tfr reactivity were determined on frozen sections from 82 patients with urothelial cancer. Relevant clinical material was reviewed to establish correlations with the degree of atypia and invasion. RESULTS--Morphologically normal urothelium, whether derived from controls or patients with cancer, exhibited a low Ki67 index (less than 0.1%) and weak receptor reactivity. In transitional cell carcinomas (TCCs) the Ki67 index was increased: it ranged between 0.7% and 10% in non-invasive and exceeded 10% in 88% of the invasive TCCs. Strong positive reactions for EGFr were seen only in invasive TCCs, but in 47% of invasive TCCs the EGFr was not "overexpressed" and did not match the Ki67 index. A better correlation was found between the Ki67 index and the Tfr which was positive in 26% of the non-invasive and in 71% of the invasive tumours. All three variables were increased in severe atypia but varied considerably in lesser degrees of atypia. CONCLUSIONS--Despite the absence of a close correlation, accelerated growth and enhanced receptor expression were characteristic of invasive cancers. These results suggest that the growth rate in TCCs is not causally related to overexpression of growth factor receptors but that the latter is an abnormality which may accompany the malignant phenotype.